Kepatuhan Syariah pada Akad Musyarakah Mutanaqishah di Bank Syariah di Indonesia - Setiawan Bin Lahuri; Fina Nurafni; Alya Zhafirah Nasywa (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Musyarakah Mutanaqishah (MMQ) is a form of hybrid contract and an alternative Sharia-compliant financing model for asset and home ownership. Despite its advantages such as shared ownership, profit sharing, rental cost flexibility, and resilience against economic volatility its implementation in Indonesia remains limited. This is due to low public awareness, and legal and operational challenges. This study aims to explore the strengths of MMQ and evaluate its compliance with Sharia principles, particularly within the framework of hybrid contracts. Employing a qualitative descriptive method through library research that includes books, journals, and scholarly articles, this research finds that MMQ aligns with Sharia law. It combines three permissible contracts: musyarakah (partnership), ijarah (leasing), and ba’i (sale). MMQ also adheres to the boundaries set for hybrid contracts, such as avoiding riba, legal contradictions, and prohibited objectives. Consequently, MMQ is considered a legitimate and Sharia-compliant financing structure. The study recommends the broader application and development of MMQ as a fair and sustainable alternative for Islamic financing in the Indonesian banking sector.